2016
DOI: 10.1016/s0020-1383(16)30011-0
|View full text |Cite
|
Sign up to set email alerts
|

Bone graft substitutes and bone morphogenetic proteins for osteoporotic fractures: what is the evidence?

Abstract: Despite improvements in implants and surgical techniques, osteoporotic fractures remain challenging to treat. Among other major risk factors, decreased expression of morphogenetic proteins has been identified for impaired fracture healing in osteoporosis. Bone grafts or bone graft substitutes are often used for stabilizing the implant and for providing a scaffold for ingrowth of new bone. Both synthetic and naturally occurring biomaterials are available. Products generally contain hydroxyapatite, tricalcium ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 46 publications
(33 reference statements)
0
16
0
3
Order By: Relevance
“…There is a great requirement for additional and affordable anabolic treatments to remedy impaired fracture healing. The evidence supporting the close association of BMPs with bone metabolism and the identification of the role of BMPs in the process of fracture healing and the pathogenesis of osteoporosis makes them attractive target molecules for the development of anabolic therapies for the prevention as well as for the treatment of osteoporotic fractures (29,30). Consistent with other studies, which have reported enhanced fracture repair and stimulated early new bone formation with rhBMP-2 treatment in ovariectomized rats (7,8), the present study indicated that rhBMP-2 has a positive effect on fracture healing in estrogen-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…There is a great requirement for additional and affordable anabolic treatments to remedy impaired fracture healing. The evidence supporting the close association of BMPs with bone metabolism and the identification of the role of BMPs in the process of fracture healing and the pathogenesis of osteoporosis makes them attractive target molecules for the development of anabolic therapies for the prevention as well as for the treatment of osteoporotic fractures (29,30). Consistent with other studies, which have reported enhanced fracture repair and stimulated early new bone formation with rhBMP-2 treatment in ovariectomized rats (7,8), the present study indicated that rhBMP-2 has a positive effect on fracture healing in estrogen-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…60 Bone morphogenic proteins and biomaterials may become useful adjuncts as BMPs are thought to be involved in the development of osteoporosis, but at this stage the literature is limited to preclinical trials. 61 It seems that current opinion will concur that it does not matter what technique of fixation is employed, or which augmentation method utilised. Good outcomes will still rely on anatomic reduction of the tuberosities and the humeral head.…”
Section: Augmentationmentioning
confidence: 99%
“…Entre sus propiedades destacan su fácil obtención, capacidad de osteoconducción, rápida absorción y fácil modelado. Sin embargo, diferencias en la morfología y estructura de sus cristales, en la porosidad, en las propiedades mecánicas y en la constitución química del SC pueden alterar significativamente sus propiedades biológicas (2,5,16) . Además, se han descubierto muchos efectos adversos y ausencia de efectos, en parte debidos a su rápida resorción.…”
Section: Sulfato De Calcio (Sc)unclassified
“…El potencial osteogénico y osteoinductivo de las BMP ha sido ampliamente validado, con tasas de fusión similares al hueso autólogo. Solo se ha aprobado el uso de BMP-2 para fusión lumbar y fracturas abiertas de tibia, y BMP-7 para pseudoartrosis de tibia (2,10,16) . Se consideran las moléculas más potentes en la inducción de la consolidación ósea, pero a pesar de la evidencia de las BMP, no dominan las estrategias para la regeneración ósea debido a diferentes cuestiones como el limitado conocimiento de sus mecanismos funcionales, la poca claridad en relación con la dosis ideal, los prerrequisitos necesarios para su éxito (disponibilidad de las células osteoprogenitoras en la fractura o pseudoartrosis o la necesidad de un adecuado aporte sanguíneo) (10) o los altos costes.…”
Section: Proteínas Morfogenéticasunclassified
See 1 more Smart Citation